The Site of the Social A Philosophical Account of the Constitution of Social Life and Change - Schatzki, Theodore R. (Penn State University Press, 2002)
Inspired by Heidegger's concept of the clearing of being, and by Wittgenstein's ideas on human practice, Theodore Schatzki offers a novel approach to understanding the constitution and transformation of social life. Key to the account he develops here is the context in which social life unfolds-the ";site of the social";-as a contingent and constantly metamorphosing mesh of practices and material orders. Schatzki's analysis reveals the advantages of this site ontology over the traditional individualist, holistic, and structuralist accounts that have dominated social theory since the mid-nineteenth century. A special feature of the book is its development of the theoretical argument by sustained reference to two historical examples: the medicinal herb business of a Shaker village in the 1850s and contemporary day trading on the Nasdaq market. First focusing on the relative simplicity of Shaker life to illuminate basic ontological characteristics of the social site, Schatzki then uses the sharp contrast with the complex and dynamic practice of day trading to reveal what makes this approach useful as a general account of social existence. Along the way he provides new insights into many major issues in social theory, including the nature of social order, the significance of agency, the distinction between society and nature, the forms of social change, and how the social present affects its future